Management accounting for business - Drury, Colin (United Kingdom : Cengage Learning, 2009)
Aimed at non-accounting management students, this textbook offers a thorough introduction to management accounting, approaching the subject from a managerial perspective, without sacrificing accuracy or detail
1. Introduction to management accounting -- 2. An introduction to cost terms and concepts -- 3. Cost-volume-profit analysis -- 4. Measuring relevant costs and revenues for decision-making -- 5. Pricing decisions and profitability analysis -- 6. Capital investment decisions: appraisal methods -- 7. Cost assignment -- 8. Activity-based costing -- 9. The budgeting process -- 10. Management control systems -- 11. Standard costing and variance analysis -- 12. Divisional financial performance measures -- 13. Transfer pricing in divisionalized companies -- 14. Strategic cost management -- 15. Strategic performance management
Earlier eds. have title: Management accounting for business decisions
Includes bibliographical references and index
Keywords: Managerial accounting; Managerial economics -- Problems, exercises, etc